Ratiometric Measurements of Adiponectin by Mass Spectrometry in Bottlenose Dolphins (Tursiops truncatus) with Iron Overload Reveal an Association with Insulin Resistance and Glucagon - Neely, Benjamin A.; Carlin, Kevin P.; Arthur, John M.; McFee, Wayne E.; Janech, Michael G. (Frontiers in Endocrinology, 2013)
High molecular weight (HMW) adiponectin levels are reduced in humans with type 2 diabetes and insulin resistance. Similar to humans with insulin resistance, managed bottlenose dolphins (Tursiops truncatus) diagnosed with hemochromatosis (iron overload) have higher levels of 2 h post-prandial plasma insulin than healthy controls. A parallel reaction monitoring assay for dolphin serum adiponectin was developed based on tryptic peptides identified by mass spectrometry. Using identified post-translational modifications, a differential measurement was constructed. Total and unmodified adiponectin levels were measured in sera from dolphins with (n=4) and without (n=5) iron overload. This measurement yielded total adiponectin levels as well as site specific percent unmodified adiponectin that may inversely correlate with HMW adiponectin. Differences in insulin levels between iron overload cases and controls were observed 2 h post-prandial, but not during the fasting state. Thus, post-prandial as well as fasting serum adiponectin levels were measured to determine whether adiponectin and insulin would follow similar patterns. There was no difference in total adiponectin or percent unmodified adiponectin from case or control fasting animals. There was no difference in post-prandial total adiponectin levels between case and control dolphins (mean ± S.D.) at 763 ± 298 and 727 ± 291 pmol/ml, respectively (p = 0.91); however, percent unmodified adiponectin was significantly higher in post-prandial cases compared controls (30.0 ± 6.3 versus 17.0 ± 6.6%, respectively; p = 0.016). Interestingly, both total and percent unmodified adiponectin were correlated with glucagon levels in controls (r = 0.999, p < 0.001), but not in cases, which is possibly a reflection of insulin resistance. Although total adiponectin levels were not significantly different, the elevated percent unmodified adiponectin follows a trend similar to HMW adiponectin reported for humans with metabolic disorders.